Fiction in literary and television reportage - narration or simple lie? - Szwajcer, Diana (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
The article presents review of opinions concerning fiction in literary and TV reportage. The author focuses on definitions and literary origins of this journalist genre. The paper proves that there is a difference between manipulation in media and artistic expression. The author also proves that final decision whether journalist is dependable or not depends on the public and its perception. From journalistic ethics point of view, it is important to be transparent in documentary work and to make an honest agreement between the author and audience